The development of past and future life stories in adolescence: Overall emotional tone, coherence and life script events. Issue 2 (5th January 2021) - Ramsgaard, Stine B.; Bohn, Annette
Abstract : Research has shown that identity in adolescence takes the shape of a coherent life story that integrates the past with the present self and provides meaning and purpose in the person's life. One stable feature of narrative identity identified in adults is emotional tone. Here, the development of emotional tone in life stories was investigated across childhood and adolescence. A total of 142 adolescents aged 10 to 14 years wrote about their past weekend, their past and future life stories and generated a cultural life script. Across age groups, adolescents told past life stories that were overall mixed (both positive and negative) or moderately positive in emotional tone, and future life stories that were positive or highly positive. In relation to life story development, we replicated findings on age‐related development of life story coherence in both past and future life stories in 10–14‐year‐olds. Lastly, the study highlights the link between life story coherence and cultural life script abilities. Cultural life script typicality was linked to life story coherence for both past and future life stories and across all age groups, and a majority of events mentioned in future life stories overlapped with cultural life script events.